Non-traumatic Limping in the Child: A Pediatric Rheumatologist Perspective on Etiology, Clinical Evaluation, Laboratory Diagnosis, and Diagnostic Algorithms using Musculoskeletal Ultrasound (MSUS) - Harjacek, Miroslav (Current Pediatric Reviews, 2024)
Limping refers to an asymmetrical gait that deviates from the typical gait pattern expected for a child of a certain age. In most children, limping is caused by a mild, self-limiting event, such as a contusion, strain, or sprain. However, a child's limping is always a pathological finding that poses a particular diagnostic challenge and necessitates a thorough assessment. The pediatrician must weigh a wide range of acute and chronic potential causes of a non-traumatic limp, including infection, neoplasia, and chronic inflammatory disorders. A thorough history and clinical examination will help us arrive at the correct diagnosis. Understanding the typical gait is essential to recognizing and correctly interpreting the disordered one. The examination of child limping involves using a variety of diagnostic methods. Efficient and cost-effective diagnosis and treatment of the underlying condition requires a systematic approach. This review provides the pediatric rheumatologist perspective and approach for evaluating non-traumatic limp in children, with a focus on the use of point-of-care (PoC) musculoskeletal ultrasound (MSUS) as a crucial tool in daily practice.
Keywords: juvenile idiopathic arthritis